Recommendations for Hepatitis B Immunoglobulin and Antiviral Prophylaxis Against Hepatitis B Recurrence After Liver Transplantation - Akarsu, Mesut; Onem, Soner; Turan, Ilker; Adali, Gupse; Akdogan, Meral; Akyildiz, Murat; Aladag, Murat; Balaban, Yasemin; Danis, Nilay; Dayangac, Murat; Gencdal, Genco; Gokcan, Hale; et al. (Turkish Journal of Gastroenterology, 2021)
The combination of hepatitis B immunoglobulin and potent nucleos(t)ide analogs after liver transplantation is considered as the standardof care for prophylaxis against hepatitis B virus recurrence. However, the recommended doses, route of administration, and durationof HBIG administration remain unclear. Moreover, hepatitis B immunoglobulin-free prophylaxis with potent nucleos(t)ide analogs hasshown promising disease outcomes in preventing hepatitis B virus recurrence. The current recommendations, produced by the TurkishAssociation for the Study of the Liver, Acute Liver Failure and Liver Transplantation Special Interest Group, suggest a reduced need forhepatitis B immunoglobulin administration with effective long-term suppression of hepatitis B virus replication using potent nucleos(t)ide analogs after liver transplantation.